Estimation of Frequencies of Different ’Form’s of Illustration in Two Developmental Anatomy Textbooks Commonly Recommended to the Medical Undergraduates of Bangladesh - Uddin, Md Mesbah; Shamim, Khondkar Manzare (Journal of Dhaka National Medical College & Hospital, 2016)
Context: Medical education has entered a new era at all levels. Innovations are being in introduced in teaching-learning methods and tools. Developmental Anatomy is an intensely visual subject for many medical students, as they must conceptualise a series of complex developmental events that occur over a period of time. Effective teaching materials are not found in most of the institutions. The illustrations can be used as a handy tool to understand the complex developmental events and mechanisms. Objectives: To analyse the presentation of illustrations in two Developmental Anatomy textbooks commonly recommended to the medical undergraduates of Bangladesh in order to determine the frequencies of different 'form's of illustration. Design, place and period of the study: The present study was a descriptive observational study involving quantitative analyses. It was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between January 2008 to December 2008. Materials and methods: Two most commonly recommended textbooks to the medical undergraduates of Bangladesh were selected for analysing their presentation of illustrations. Six 'form's of illustration (diagram, photograph, photomicrgraph, scanning electron microgaph, diagnostic image and others) based on how they have been created and how they look like were identified. The frequency of each 'form' was also determined. Results: The mean frequency of a specific 'form' of illustration is the highest for 'diagram' (87.35 ±7.83)%, and the lowest for 'scanning electron micrograph' (1.32 ± 1.87)%. Conclusions: Incorporating the findings of the present study with the modern ideas and trends in teaching-learning of Developmental Anatomy and Genetics, suggestions could be formulated on improving the methods of teaching-learning of Developmental Anatomy and Genetics in Bangladesh J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 41-46